EIB Working Paper 2021/01 - Towards a new growth model in CESEE Convergence and competitiveness through smart, green and inclusive investment (Volume 2021/01) - Gereben, Áron (European Investment Bank, 2021)
The factors behind the pre-crisis growth model of the Central, Eastern and South-Eastern European EU countries (CESEE) region - skilled yet affordable labour force, foreign direct investment, imports of productivity-enhancing technology - are having less effect, but are yet to be substituted. This paper proposes a new growth model centred around a shift towards more home-grown innovation, digitalisation, climate change mitigation and a strong focus on skills, labour and social inclusion, to leave the middle-income trap behind for good and to boost economies' growth prospects in a post-COVID world. Based on analysis of firm-level data, it highlights the prerequisites of making this transition happen.